The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/bonekey.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

Adult Tph2 knockout mice without brain serotonin have moderately elevated spine trabecular bone but moderately low cortical bone thickness

Abstract: Disruption of serotonin synthesis in neurons and the periphery by knockout (KO) of mouse genes for tryptophan hydroxylases (peripheral Tph1 and neuronal Tph2) has been claimed to decrease (Tph2 KO) and increase (Tph1 KO) bone mass. In this report, adult male and female Tph2 KO mice were observed to have elevated spine trabecular bone. Female Tph2 KO mice have reduced midshaft femur cortical bone thickness. Bone mass was normal in male and female Tph1 KO mice examined as part of a Tph1/Tph2 double knockout (DKO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Components of the serotonin signaling pathway are present on osteoclasts, osteoblasts, and osteocytes 20 . However, there is little consensus on the role of serotonin in the regulation of bone mass 2123 . Pups exposed to fluoxetine throughout pregnancy and lactation had elevated concentrations of serum serotonin compared to control pups.…”
Section: Discussionmentioning
confidence: 99%
“…Components of the serotonin signaling pathway are present on osteoclasts, osteoblasts, and osteocytes 20 . However, there is little consensus on the role of serotonin in the regulation of bone mass 2123 . Pups exposed to fluoxetine throughout pregnancy and lactation had elevated concentrations of serum serotonin compared to control pups.…”
Section: Discussionmentioning
confidence: 99%
“…Gut is the major site of serotonin production, through the actions of the enzyme tryptophan hydroxylase (TPH1). Some microbes produce serotonin and several studies demonstrate that gut microbiota induce host serotonin production in the gut 7,45 , however the majority of reports suggest that the absence of gut serotonin production in Tph1 −/− mice has little effect on bone physiology 4648 . Therefore, whether induction of serotonin is involved in microbiota modulation of bone phenotype still needs further investigation.…”
Section: Mechanisms Underlying Microbiota-mediated Effects On Bonementioning
confidence: 99%
“…However, an association among LRP5 deficiency, circulating 5HT and bone loss has not been reproduced in mice with osteocyte-specific expression of inducible Lrp5 mutations that cause high and low bone mass phenotypes in humans [ 3 ]. Further, association between circulating serotonin and bone mass has not been unequivocally confirmed in different mouse knockout models (global knockouts of TPH1 and TPH2, LRP5) [ 4 6 ]. De Vernejoul and colleagues revisited the bone phenotype in mice with genetic deletion of peripheral 5HT-synthesizing enzyme tryptophan hydroxylase-1 ( TPH1 -/- ) and showed that osteoclasts synthesize 5HT which acts to induce osteoclast precursor differentiation in a local micro-serotoninergic system via a mechanism of RANKL-induced osteoclast formation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%